Fenomena Sosial Mikro-Makro Nahdlatul Wathan Era Orde Baru - Jamiluddin, Jamiluddin (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2018)
This article discusses how Nahdlatul Wathan is prepared to care for the Islamic mission and the future of the country. Also include in some sub, this article examines the effort was done by Nahdlatul Wathan manifest his existence, for example, as system engineering organization that carefully conditioned with deep and widespread benefit standard. Study of integration efforts of the entire element, both micro as well as macro Nahdlatul Wathan became a staple part because that social phenomenon conspicuous in the dynamics of the Nahdlatul Wathan. Answering some doubts, trigger the interest analyze the awareness of Nahdlatul Wathan more conical in the post national tragedy, G-30-S PKI. In more detail, the author loads the perception ofNahdlatul Wathan positioning the national tragedy above as a threat of the prestige of Republic Indonesia. The author then observe that the Nahdlatul Wathan at the beginning of the new orde era as it has come to a turning point to do something for his country and nation without support of hope space